ANALYSIS OF AUTONOMY FACTOR OF ENTREPRENEURSHIP INTENTION WITH REFERENCE TO STUDENTS OF SELECTED UNIVERSITIES OF NORTH-INDIA - Tusshar Mahajan; Vikas Arora (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2018)
Entrepreneurship leads to economic growth and social development. Entrepreneurship is a risk-taking activity which needs dedication and focused approach. In case of students, starting a new venture is not an easy task, due to inclusion of high risk and uncertain future. There are many factors that trigger Entre-preneurship Intention of students; Autonomy is one such factor. The present study analyzed autonomy factor of entrepreneurship intentions of students with reference to North-India region. Students were found to have more inclination towards entrepreneurship with respect to autonomy factor. The study implied that Non-Metropolitan area students and especially Non-Metropolitan female students are more inclined towards entrepreneurship due to aspiration of autonomy.